Freiheitsschauplatz (Nomos Verlagsgesellschaft mbH & Co. KG, 2025)
Three revolutions in three decades; a vibrant civil society and the epitome of resilience—Ukrainian society is as impressive and diverse as it is largely unknown in Germany. Who are the Ukrainians; and how do they see themselves and their country in Europe? How have the revolutions; the upheaval of the 1990s and the developments since the Maidan shaped Ukrainian society? What is the significance of Europeanisation and the decades-long conflict with Russia to Ukrainian society? In this book; German and Ukrainian experts explain Ukrainian society for the first time; it is also the first German-language publication of a sociology of Ukraine.